2001
DOI: 10.1016/s0378-4371(01)00158-3
|View full text |Cite
|
Sign up to set email alerts
|

Percolation line of self-bound clusters in supercritical fluids

Abstract: We predict that self-bound clusters of particles exist in the supercritical phase of simple fluids. These clusters, whose internal temperature is lower than the global temperature of the system, define a percolation line that starts at the critical point. This line should be physically observable. Possible experiments showing the validity of these predictions are discussed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 28 publications
4
43
0
Order By: Relevance
“…The gas-liquid coexistence curve obtained by Panagiotopoulos 37 and the MC liquid-solid coexistence curve of Hansen and Verlet 38 are also shown. The MD results for the HE criterion are similar to those obtained by Campi et al 30 These authors consider that the system is on the percolation line if the second moment of the cluster size distribution that excludes the largest cluster n ′ (s) reaches its maximum. In Fig.…”
Section: Molecular Dynamics Calculationssupporting
confidence: 83%
See 2 more Smart Citations
“…The gas-liquid coexistence curve obtained by Panagiotopoulos 37 and the MC liquid-solid coexistence curve of Hansen and Verlet 38 are also shown. The MD results for the HE criterion are similar to those obtained by Campi et al 30 These authors consider that the system is on the percolation line if the second moment of the cluster size distribution that excludes the largest cluster n ′ (s) reaches its maximum. In Fig.…”
Section: Molecular Dynamics Calculationssupporting
confidence: 83%
“…27 It should be mentioned that the HE criterion has been considered in MD studies of small clusters and the critical percolation behavior of Lennard-Jones fluids by several authors. 28,29,30 It has been suggested that the percolation line-the line that separates the temperature-density phase diagram into percolated and non-percolated states-might be experimentally observable. 30,31 Moreover, cluster analysis based on this criterion seems to be useful in locating the gas-liquid coexistence curve.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Zipf's laws. As mentioned before, various theories of cluster formation (Fischer droplets [10], lattice-gas [6], Lennard-Jones fluids with Hill's clusters [11], percolation [8]), predict power laws c.s.d. with τ ≃ 2 at the corresponding critical points.…”
mentioning
confidence: 99%
“…We will show that the observation of Fisher scaling does not allow to determine the location of the critical point. Critical behaviors are observed on a line at supercritical density [11] which extends inside the coexistence region [12,13] due to finite size effects. We suggest that the inadequacy of the Fisher model to describe the lattice gas phase diagram comes from the Fisher independent cluster hypothesis which should be correct only at low densities and high temperatures ; indeed we demonstrate that the thermodynamics reconstructed from the Fisher partition sum coincides with the exact one only in the low density and high temperature regime.…”
mentioning
confidence: 99%